"Deregulation is so nineteen eighties, we're into 'better regulation' now": Exploring the unintended consequences of self-regulation through enterprise in the Passive Fire Protection industry. Issue 3 (10th October 2016) - Russell, Stephanie; Brannan, Matthew J.
Abstract : Purpose: The purpose of this paper is to explore how organizations operate in the absence of a clear regulatory authority in a self-regulating environment. Significant moves towards self-regulation by various political administrations, together with successive waves of deregulation raise questions about the ability and effectiveness of industries and markets to regulate their own behaviour. This is a topical political and social concern with governments often appearing to favour self-regulation as opposed to the constitution of an official regulator. The absence of a regulator and the possibility of voluntary compliance raise a number of issues for the way in which organizations operate and the consequences, both intended and otherwise for organizations and society at large. Design/methodology/approach: Empirically the authors explore the case of an industry leader within the Passive Fire Protection industry, as it adjusts to an increasingly self-regulated market environment. The authors document how organizational members make sense of the regulatory environment and the behaviour of actors within it. Findings: The authors find that discourses of enterprise that underpin self-regulation permit actors a choice between compliance and non-compliance. Whilst also noting the prevalence of notions of morality in terms of how actors make sense of both compliant and non-compliant behaviour. Despite common sense notions that morality is seldom clear cut or unambiguous, the case study reveals that frameworks for understanding behaviour allow participants within the industry to make very clear demarcations between moral (compliant) and amoral (non-compliant) behaviour. Originality/value: The authors learn how those that are compliant within the industry come to question the effectiveness of the regime to which they comply, thus ultimately undermining the integrity of the regime. In the absence of a strong regulatory regime, some agents draw upon notions of enterprise to justify an individualist, economic and pragmatic approach that makes non-compliance permissible. Thus the discourse of enterprise is present in the justification of both "moral" and "amoral" behaviour, this leads the authors to question the wisdom of policy that promotes the idea of enterprise as effectively ensuring compliance.